Antidepressant drug use among adolescents during 2004–2013: a population‐based register linkage study. (29th August 2016) - Hartz, I.; Skurtveit, S.; Hjellvik, V.; Furu, K.; Nesvåg, R.; Handal, M.
Abstract : Objective: To study trends in use of antidepressants (ADs) by adolescents, and psychiatric morbidity and use of other psychotropic drugs as a measure of psychiatric comorbidity. Methods: One‐year prevalence of AD drug use was analyzed for 13‐ to 17‐year‐old Norwegians during 2004–2013. Use of other psychotropic drugs and specialist healthcare services was analyzed for incident AD users in 2012, using linked data from the Norwegian Prescription Database and the Norwegian Patient Register. Results: The 1‐year prevalence of AD drug use increased from 6.4/1000 to 9.1/1000 during 2004–2013, with the steepest increase from 2010, particularly among girls. The highest prevalence was found in 17‐year‐old girls (17.8/1000 in 2010, 27.5/1000 in 2013). Of incident AD drug users in 2012, 84.4% had been in contact with specialist health care. As the first drug, 78.4% were prescribed a selective serotonin reuptake inhibitor. The most common types of other psychotropic drugs were melatonin (24.6%), antipsychotic drugs (13.2%), stimulants (8.8%), and anxiolytics (6.0%). Conclusions: Use of ADs among adolescents has increased over the last 3–4 years, particularly among 16‐ to 17‐year‐old girls. A total of 85% of incident users had been in contact with specialist health care, which may indicate that drug‐therapy is used by adolescents with more severe symptoms.